A screw based methodology for instantaneous dynamic balance. (November 2019) - de Jong, J.J.; van Dijk, J.; Herder, J.L.
Highlights: Unified force and moment balance in a single pose without manipulation of equations. Geometric interpretation of feasibility bounds for selecting inertial parameters. A novel 2-DOF demonstrator shows a 95% reduction of the shaking forces and moments. Abstract: Fast-moving industrial robots exert large varying reaction forces and moments on their base frame, inducing vibrations, wear and accuracy degeneration. These shaking forces and moments can be eliminated by a specific design of the mass distribution of the robot links, resulting in a dynamically balanced mechanism. Obtaining the conditions for dynamic balance proves to be a hurdle even for simple planar parallel mechanisms due to the required inclusion and inspection of the kinematic relations. In this paper, a screw theory based methodology is presented, which gives and solves the necessary instantaneous dynamic balance conditions for planar and spatial mechanisms in an uniform and geometrical manner. Instantaneous dynamic balance yields a pose in which robot accelerations induce no shaking forces and moments. This is interpreted as an intersection point of multiple reactionless paths. This method is applied to a 2-DOF planar mechanism, named the Fuga I, for which it resulted in two perpendicularly intersecting reactionless paths, intersecting in the middle of the workspace. Experiments on this demonstrator validated the instantaneous dynamic balance by showing a reduction of approximately 95% of the peak-to-peak shaking forces and moments over the intersecting reactionless paths.